Eudaimonisme og anti-eudaimonisme - Berg, Kenneth (Dansk Teologisk Tidsskrift, 2010)
The quality of disinterestedness is generally thought to be the defining feature of the moral act. As a result, much of modern moral thinking promotes some idea of self-sacrifice. It is the contention of the present article that this tendency is unfortunate. At the same time, it suggests that the opposite view – namely that human beings are by nature ineradicably selfish – is equally problematic. The article traces the origins of these two positions to the quarrel over pure love at the end of the 17th century and discusses the views of its two main protagonists, François Fénelon and Jacques-Bénigne Bossuet. In the final third, the article turns to the 20th century, particularly to German philosopher Robert Spaemann. It thereby includes a suggestion of how the modern paradigm of disinterestedness may be dissolved through a phenomenological analysis of love.